Vozes literafro-brasileira : promovendo a identidade e a diversidade na escola - Oliveira, Valdeny Lopes de (2024)
This TCF dissertation (Final Conclusion Paper), entitled “Afro-Brazilian Literary Voices: promoting identity and diversity at school” aims to contribute to the literary literacy and critical formation of students in Elementary School II, based on short stories by Afro-Brazilian writers. Brazilians, Cristiane Sobral (2014) and Miriam Alves (2021), who discuss topics related to the human condition of a portion of society, such as racism in various spaces, including schools. In addition to using the literary text with a focus on subjective reading to develop reflection/action in the construction of affirmative actions in anti-racist and identity education. In this sense, a pedagogical notebook was developed as an educational resource that makes it possible to enhance the practice of literary literacy and the implementation of law 10.639/03, which is still rarely discussed in basic education schools. Therefore, the first chapter of this work is theoretically based on studies carried out on reading and literary reading, the Common National Base-BNCC (2018); Soares (2006); Solé (1998) Cosson (2014), Kleiman (1995); Colomer (2003); Cândido (2004); Cruz (2012); Rouxel (2013); among others. In the second chapter focused on Afro-Brazilian literature, Munanga (2012); Duarte (2022); Cuti (2010); National Curricular Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture and Law 10.639/03; between others. In the last chapter, the methodological procedures and instruments, action research and results of the didactic sequence are considered, based on Cosson's basic sequence method (2014), such as: motivation, introduction, reading and interpretation. The literary workshops were held in a municipal public school in the city of Euclides da Cunha - Bahia, in a 9th year class of elementary school II, which involved experiences with Afro-Brazilian literary reading, with the construction of some genres that motivate learning through literary and racial literacy.